Unveiling the good and the bad of being a taxi driver and educating for health (Research, Society and Development, 2020)
Objective: to investigate positive and negative aspects of the taxi driver profession, in the perception of who works. Method: the cross-sectional and descriptive research, quantitative approach, was developed with 45 motorcycle taxi drivers from a municipality in the interior of Rio Grande do Sul, in 2017. A structured questionnaire was used as an instrument of data collection. Data were analyzed using descriptive statistics and frequency distribution. Results: 84% of the participants enjoy their profession, as the time is free and can reconcile other activities. The main damages to physical health pointed out by them were abrasions, upper limb fracture, lower limb and cost. And, the main risk agents are ergonomic, because of the body position used on the motorcycle that causes back pain; biological by exposure to animal bites, physical by exposure to rain, sun and cold and psychosocial by the feeling of devaluation of society in relation to its activity. Use a facebook page as a means of health education for this worker. Conclusion: health education and social valorization campaigns can prevent injuries to these workers, promote their health and help the population to know as vulnerabilities, adding value to life.